Becoming Prominent: Regional Leadership in Upper Canada, 1791-1841 - Patterson, Graeme (Labour / Le Travail, 1991)
The article reviews the book, "Becoming Prominent: Regional Leadership in Upper Canada 1791-1841," by J. K. Johnson.
Keywords: BECOMING Prominent: Regional Leadership in Upper Canada 1791-1841 (Book); BOOKS -- Reviews; JOHNSON, J. K.; Leadership; Nonfiction